The Oriental hornet, Vespa orientalis Linnaeus, 1771 (Hymenoptera, Vespidae): diagnosis, potential distribution, and geometric morphometrics across its natural distribution range - Smith-Pardo, Allan H.; Altamiranda-Saavedra, Mariano; Polly, P. David (Frontiers in Insect Science, 2024)
We present a short review of the biology, diagnostic characters, and invasiveness of the Oriental hornet, Vespa orientalis. We also performed an analysis of the shape of the forewings (geometric morphometrics) of different geographic groups along their native distribution and their potential geographical distribution using the Maxent entropy modeling. Our results show a wide potential expansion range of the species, including an increase in environmentally suitable areas in Europe, Asia, and Africa but more especially the Western Hemisphere, where the species was recently introduced.The geometric morphometric analysis of the forewings shows that there are three different morphogroups: one distributed along the Mediterranean coast of Europe and the Middle East (MEDI), another along the Arabian Peninsula and western Asia but excluding the Mediterranean coast (MEAS), and one more in northern Africa north of the Sahara and south of the Mediterranean coast (AFRI), all of which show differences in their potential distribution as a result of the pressure from the different environments and which will also determine the capacity of the different morphogroups to successfully invade new habitats.